IDENTIFICATION OF THE TYPE OF FERNS IN THE FOREST AREA OF NOONGAN VILLAGE - Yosua Linu; Helen J Lawalata; Rievo Djarang (Universitas Negeri Manado, 2023)
Ferns (Pteridophyta) are spore-forming cormophytes that can live in a variety of habitats both as epiphytes, terrestrial and aquatic. In the forest area of Noongan Village, many potentials play an important role in developing forest ecosystems. One such potential is ferns. The results of the study were eight types of ferns in the forest area of Noongan village which were divided into two plots of 50x50 meters at different heights, namely plot I at an altitude of 610 masl with a total of 380 ferns with the percentage: Paku Garuda (Pteridium aquilinium) 0.20 %, Elephant fern (Angiopetris avecta Hoofm) 0.01%, Red rane fern (Selaginella australis) 0.01%, Paku Kikir (Stenosomia Sp.) 0.14%, Ferret fern (Nephrolepis biserrataSchott.) 0, 21%, cecerenean fern (Nephrolepis falcata) 0.16%, suplir fern (Adiantum.) 0.12%, andam fern (Dicranopetris linearis) 0.12%. And plot II at an altitude of 869 meters above sea level with a total of 179 ferns with a percentage of: Garuda fern (Pteridium aquilinium) 0.21%, elephant fern (Angiopetris avectaHoofm) 0.01%, miserly fern (Stenosomia Sp.) 0, 17%, Paku harupat (Nephrolepis biserrate Schott.) 0.21%, Paku cecerenean (Nephrolepis falcata) 0.15%, Suplir (Adiantum.) 0.10%, Paku andam (Dicranopetris linearis) 0.12%. In the plot I, the types and number of ferns were higher than the types and numbers of ferns in plot II. No red fern (Selaginella australis) was found in plot II. And the plant species Paku Harupat (Nephrolepis biserrata Schott). The red fern has the highest number, and the red fern (Selaginella australis.) has the least amount. The difference in altitude greatly affects the surrounding environment. So that these differences greatly affect the number of types and numbers of ferns